PROGRESSIVE PERSONAL INCOME TAX: ADVANTAGES AND DISADVANTAGES - N. L. Kaznacheeva; D. E. Lapov (Финансы: теория и практика, 2017)
Article Retracted.The paper studies the introduction of progressive personal income tax rates in Russia. The objective set in the scope of the research is to determine the most significant socio-economic implications of the introduction. The research focuses on the analysis of the impact the progressive tax rates might have on personal incomes assuming the targeted approach widely recognized abroad as a tool for the study of government programs in the area of financial protection of the most vulnerable groups. The paper conciders constitutional principles of financial discrimination and methods to ensure it. The fiscal and socio-economic benefits of the financial discrimination measures inherent in the income tax are compared with similar measures for social transfers and property taxes; also discussed are advantages and disadvantages of the targeted approach used in progressive taxation. A model of budget balance through reallocation of the opportunity cost used for progressive taxation is described. The costs of incentives being the main argument in favor of maintaining the flat income tax scale and the effects they might lead to are analyzed.The principal advantages and disadvantages in terms of private and public interests are highlighted to be taken into account when choosing measures of state regulation of the economy such as the introduction of progressive personal income taxation, increasing the role of property taxes and the introduction of or increase in the size of social transfers. The introduction of progressive taxation is analyzed from the viewpoint of the constitutional principles of the state economic regulation; it is concluded that such introduction is feasible. In part of the state regulation of the economy, arguments are provided both in favor of and against the introduction of progressive taxation. The findings of the research may be helpful to law decision makers in assessing the feasibility of the progressive personal income tax in Russia.